Re-evaluation of the Anatomical Distribution Patterns in Large Congenital Melanocytic Nevus - Aydogdu, Sevkiye; Baykal, Can (Dermatology Practical & Conceptual, 2025)
Introduction: Large congenital melanocytic nevi (LCMNs) are mainly classified according to their distribution patterns, which are thought to reflect their embryological development.Objectives: We aimed to test the validity of previously described clinical classification systems of LCMNs in a large, well-documented case series.Methods: The retrospective cohort study including 111 LCMN patients focused on the anatomical distribution of the nevus’s main mass.Results: The trunk was most commonly affected (N=68), followed by the lower extremities (N=35). When the locations of the nevi were evaluated according to the previously described 6B (bolero, back, bathing trunk, breast/belly, body extremity, body patterns) and 7B (6B with the addition of bonce pattern) classification systems, 15 showed the typical bolero pattern, 13 back pattern, 23 bathing trunk pattern, five breast/belly pattern, 25 body extremity pattern, 14 bonce (head) pattern, and one body pattern. Among the 15 patients who could not be fully classified according to these patterns, five were grouped as “hood” (head and neck) pattern, eight as “half-bathing trunk,” and two as “atypical bolero” sub-patterns. Isolated lesions on the extremities also exhibited two different sub-patterns: encircling the extremity or not.Conclusion: Most of our cases demonstrated distribution patterns consistent with the 6B and 7B classification systems. However, the isolated head and neck involvement observed in our series may be described as hood pattern. Furthermore, certain variations, such as those seen in the bathing trunk and breast/belly patterns, may be considered subgroups of these patterns. Isolated extremity lesions of LCMNs exhibited two distinct patterns. These findings suggest that, although existing classification systems provide a valuable framework, further subclassifications may be necessary to account for regional variations observed in clinical practice.